Emergence of Group A Streptococcus Strains with Different Mechanisms of Macrolide Resistance - Bingen, Edouard (American Society for Microbiology, 2002)
The mechanisms of resistance to macrolides in seven group A streptococcal (Streptococcus pyogenes) isolates that were the cause of pharyngitis in children who were unsuccessfully treated with azithromycin (10 mg/kg of body weight/day for 3 days) were evaluated. All posttreatment strains were found to be genetically related to the pretreatment isolates by random amplified polymorphism DNA analysis and pulsed-field gel electrophoresis. Two isolates had acquired either a mef(A) or an erm(B) gene, responsible for macrolide efflux and ribosomal modification, respectively. Three isolates displayed mutations in the gene encoding the L4 ribosomal protein that is part of the exit tunnel within the 50S subunit of the bacterial ribosome. In the two remaining posttreatment strains, the mechanisms of macrolide resistance could not be elucidated.